πŸ‘€

Answer :

Step-by-step explanation:

Given :-

(√3-√2)/(√3+√2)

To find :-

Rationalised form = ?

Solution:-

Given that

(√3-√2)/(√3+√2)

The denominator = √3+√2

The Rationalising factor of √3+√2 is √3-√2

On Rationalising the denominator then

=> [(√3-√2)/(√3+√2)]Γ—[(√3-√2)/(√3-√2)]

=> [(√3-√2)(√3-√2)]Γ—[(√3+√2)(√3-√2)]

=> (√3-√2)²/[(√3+√2)(√3-√2)]

=> (√3-√2)²/[(√3)²-(√2)²]

Since (a+b)(a-b) = aΒ²-bΒ²

Where , a = √3 and b = √2

=> (√3-√2)²/(3-2)

=> (√3-√2)²/1

=> (√3-√2)²

=> (√3)²-2(√3)(√2)+(√2)²

Since , (a-b)Β² = aΒ²-2ab+bΒ²

Where , a = √3 and b = √2

=> 3-2√6+2

=> 5-2√6

Hence, the denominator is rationalised.

Answer:

Rationalised form of (√3-√2)/(√3+√2) is 5 - 2√6.

Used formulae:-

  • (a+b)(a-b) = aΒ²-bΒ²
  • (a-b)Β² = aΒ²-2ab+bΒ²
  • The Rationalising factor of √3+√2 is √3-√2